Comparative Analysis of Income from Consuming Rice Farming and Seed Farming in Pelanglor Village, Kedunggalar District, Ngawi Regency: Comparative Analysis of Income from Consuming Rice Farming and Seed Farming in Pelanglor Village, Kedunggalar District, Ngawi Regency (Jurnal Pertanian Terpadu, 2025)
Ngawi Regency contributes 50% of East Java's rice food with a production of 778 thousand tons. The need for rice seeds continues to increase along with the increase in planting area with the need for rice seeds per hectare ranging from 25-29 kg/ha This research aims to 1) Analyze the income of consumption rice farms and seed breeders, 2) Analyze the factors that influence farmers in making decisions about cultivating consumption rice and seed breeders. The research methods used are income analysis and SEM-PLS analysis. The research methods used are descriptive analysis, income analysis and SEM-PLS analysis. The results of the research show the income of cultivating seed-raising rice from each 1 Ha land area is higher than consumption rice, namely IDR 36,640,080.00 with total income of IDR 62,161,724.00 and total costs of IDR 25,521,644.00. The income from consumption rice farming is IDR 26,259,133.00 with total receipts of IDR 50,065,866.00 and total costs of IDR 23,806,733.00. The results of the SEM-PLS program analysis show that the variables of cultivation technique, income and self-confidence influence farmers in choosing consumption rice farming. The variables income, capital and self-confidence influence farmers to choose seed breeding rice farming.